Penerapan Black Box Testing Berstandar ISO 29119 Pada Aplikasi Perpustakaan Dari Repositori Github - Muhtadin, Sabilal; Jodian Saputra, Shadam; Anwar, Chairul (PT Jurnal Cendekia Indonesia, 2025)
The utilization of open-source software from public repositories like GitHub is increasingly prevalent in institutional system development. However, this software is often adopted without adequate quality validation processes, posing risks of functional failure in production environments. This study aims to verify the quality of a web-based